Epidemiology and Direct Medical Cost of Osteoporotic Hip Fracture in Chile - Iván Quevedo; Juan C. Ormeño; Bunio Weissglas; Cristóbal Opazo (Journal of Osteoporosis)
The osteoporotic hip fracture is associated with a high impact on morbidity, mortality, and health expenditure. The Chilean health system is made up of a mixed care system, with the public system called FONASA and the private system called ISAPRE. The people with lower incomes are listed on FONASA and correspond to 80.8% of the population. The aims of this study were to describe the incidence of hip fracture in the Chilean population from the age of 45 years and to estimate the direct medical cost of this disease. The records of the Department of the Health Statistics and Information of the Ministry of Health were used, from which the number of national hospital discharges due to hip fractures was obtained (codes S720, S721, and S722 of the ICD-10), in adults aged 45 years or older, by sex, from 2006 to 2017. The cost of osteoporotic hip fracture treatment in the public health system was obtained from the data of the surgical treatment according to the payment method associated with diagnosis (PAD bonus). A surgical intervention budget was used in a private clinic to calculate the direct cost of osteoporotic hip fracture in the private system. Between 2006 and 2017, the number of hospital discharges due to osteoporotic hip fracture in adults aged 45 years and older has increased progressively, registering 9.583 hospital discharges for this cause in 2017, which corresponds to 50% more than those recorded in 2006, with a 3 : 1 F/M ratio. The mean annual rate of hip fractures is 148.7 per 100,000 inhabitants aged above 45 years. The individual cost of managing an osteoporotic hip fracture in the public system was USD$ 3,919, and USD$ 9,092 in the private health system. The incidence of hip fracture was comparable with data from Southern European countries and from neighboring countries, such as Argentina and Uruguay. Hospitalization cost of hip fracture in Chile was 34 million USD per year. Hip fracture constitutes a serious healthcare problem in Chile, and efforts for the prevention and management of osteoporosis are needed.